Evidence of a coupled electron-phonon liquid in NbGe2 - Hung-Yu Yang (Nature Portfolio, 2021)
It was predicted that in the regime of strong electron-phonon interactions, electrons and phonons can form a coupled non-equilibrium state, characterized by the conservation of the total momentum and by hydrodynamic transport. Here, the authors report experimental evidence for such a coupled electron-phonon liquid in NbGe2.